Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 63. Beitrag. Diptera: Limoniidae. - Mannheims, Bernard (Contributions to Entomology = Beiträge zur Entomologie, 1967)
The Limoniidae collected by the expedition to Albania by Deutsches Entomologisches Institut in 1961 total 45 specimens of 14 species. 2 of these species were found for the first time in the fauna of Albania and one is described as Erioptera (Ilisia) friesei spec. nov. The species of an earlier expedition to Albania - made in 1918 by the Austrian Naturhistorisches Museum in Vienna were included. So this first list enumerates 64 species of Limoniidae known from Albania, while about 120 species may be supposed to exist there. Nomenclatural Actsfriesei Mannheims, 1967 (Gonomyia (Ellipteroides)), spec. n. In the summary erroneusly named as Erioptera (Ilisia) friesei.